Production and Characterization of Bacterial Ghost Vaccine against Neisseria meningitidis - Randa H. Ali; Mohamed E. Ali; Reham Samir (Vaccines, 2022)
Bacterial ghosts (BGS) are empty non-living envelopes produced either genetically or chemically. This study investigated a novel chemical protocol for the production of Neisseria meningitidis ghost vaccine using tween 80 followed by a pH reduction with lactic acid. For our vaccine candidate, both safety and immunogenicity aspects were evaluated. The ghost pellets showed no sign of growth upon cultivation. BGS were visualized by scanning electron microscopy, illustrating the formation of trans-membrane tunnels with maintained cell morphology. Gel electrophoresis showed no distinctive bands of the cytoplasmic proteins and DNA, assuring the formation of ghost cells. In animal model, humoral immune response significantly increased when compared to commercial vaccine (p < 0.01). Moreover, serum bactericidal assay (SBA) recorded 94.67% inhibition compared to 64% only for the commercial vaccine after three vaccination doses. In conclusion, this is the first N. meningitidis ghost vaccine candidate, proven to be effective, economic, and with significant humoral response and efficient SBA values; however, clinical studies should be performed.